PENGARUH WORK ENVIRONMENT DAN WORK-LIFE BALANCE TERHADAP EMPLOYEE PERFORMANCE MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Erliana Indarti; Hary Soegiri; Ibnu Sutomo (Jurnal Manajemen Pendidikan, 2026)
Research simultaneously examining Work Environment, work-life balance, and job satisfaction as a mediator of Employee Performance remains scarce in Indonesian vocational school settings. At SMKN 1 Jaro, Tabalong Regency, internal data revealed an average job satisfaction rate of only 55.6%, with the physical Work Environment (44.5%) and supervisor relationships (44.8%) recording the lowest scores, while all employees attained only a 'Good' performance rating with none reaching 'Excellent' indicating systemic constraints on performance optimization. This study aims to analyze the influence of Work Environment and work-life balance on Employee Performance through job satisfaction as an intervening variable. A quantitative correlational approach was employed, involving all 29 teachers and administrative staff as a saturated sample. Data were collected via a Likert-scale questionnaire (1–5) and analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM) with SmartPLS 3. The results confirm that all seven hypotheses were supported at α = 0.05. Work Environment and work-life balance had significant positive effects on job satisfaction (T = 3.518; T = 3.680) and Employee Performance (T = 4.175; T = 2.798).